Effects and safety of Salvia miltiorrhiza on the improvement of renal function, inflammatory factors, and vascular endothelium in patients with diabetic kidney disease: a meta-analysis and systematic review - Zheng, Shuyu; Zhang, Meng; Wang, Wenkuan; Zhang, Qian; Zhang, Ning (Frontiers in Pharmacology, 2025)
ObjectiveTo elucidate the efficacy and safety of Radix et rhizoma Salvia miltiorrhiza (SM) in the treatment of Diabetic Kidney Disease (DKD), and to provide a rationale and scientific reference for the use of SM preparations in the treatment of DKD. This study is the first systematic evaluation and Meta-analysis focusing exclusively on the use of SM as a single agent in the treatment of DKD.MethodsA comprehensive search was conducted in PubMed, Web of Science, Cochrane Library, Elsevier Science Direct, CNKI, Wanfang, and VIP databases, covering the timeframe from the inception of the journals to May 2025. The search was restricted to randomized controlled trials conducted within the past decade that investigated the use of SM/SM preparations as a treatment for DKD. The control group received conventional interventions, while the intervention group received SM/SM preparations. Endnote 20 and Excel were employed for literature management and data organization, and Revman 5.3 and Stata 18 software were used for the analyses.ResultsThis study involved 21 RCTs with 1970 participants. The results demonstrated that SM preparations led to reductions in serum creatinine (Scr), blood urea nitrogen (BUN), urinary albumin excretion rate (UAER), 24-h urinary total protein (24 h-utp), C-reactive protein (CRP), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and endothelin-1 (ET-1) levels among patients with DKD (P < 0.05). Moreover, these preparations elevated flow-mediated vasodilation (FDM), showcasing their clinical effectiveness over the control group (P < 0.05). Notably, the safety profile remained sound, with no significant differences in adverse event rates between the two groups (P > 0.05).ConclusionThese results indicate that SM preparations could considerably improve renal and vascular endothelial function while simultaneously decreasing harmful inflammatory markers in patients with DKD, which allow it serve as a safe and effective therapeutic option.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/#recordDetails, identifier CRD42024623452.